A quantum field theory for the interaction of pions and rhos - Moodley, Preshin (Department of Physics, 2017)
We extend the Kroll-Lee-Zumino model in its particle content to include the charged rho vector mesons and the neutral pion meson. This entailed using the larger SU(2) gauge group. The masses for the vector mesons were generated via spontaneous symmetry breaking using the Higgs mechanism. The Lagrangian was then quantized and gauge fixed using the generalized class of Rɛ gauges. Tree scattering lengths were calculated for pion-pion scattering and the values for the a₀⁰ and a₀² scattering lengths are found to be comparable with experiment. The one particle irreducible diagrams that contribute to the one loop corrections to the tree scattering lengths are renormalized.